2017
DOI: 10.1136/annrheumdis-2017-211781
|View full text |Cite
|
Sign up to set email alerts
|

Successful reduction of overexposure in patients with rheumatoid arthritis with high serum adalimumab concentrations: an open-label, non-inferiority, randomised clinical trial

Abstract: NTR3509; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 18 publications
3
58
0
Order By: Relevance
“…A recent systematic review found very limited and low‐quality information on potential markers for successful dose reduction or discontinuation of biologic agents in RA . Some studies with adalimumab have suggested that a higher trough level of adalimumab may be a good marker for reducing the dose; however, in our study, we did not determine drug serum levels .…”
Section: Discussionmentioning
confidence: 72%
“…A recent systematic review found very limited and low‐quality information on potential markers for successful dose reduction or discontinuation of biologic agents in RA . Some studies with adalimumab have suggested that a higher trough level of adalimumab may be a good marker for reducing the dose; however, in our study, we did not determine drug serum levels .…”
Section: Discussionmentioning
confidence: 72%
“…In this case, the assay analyte will not be detectable and the complex should first be dissociated to make the analyte accessible for detection. L'Ami et al showed that quantitation of the therapeutic anti-TNF-α antibody, adalimumab, can be used to determine dosing intervals and to individualize disease control in patients with rheumatoid arthritis [20]. We integrated an acidification step into the ELISA assay, and in this way increased tolerability towards high concentrations of drug and/or ADA.…”
Section: Discussionmentioning
confidence: 99%
“…and simultaneously increase therapeutic effectiveness [19]. L'Ami et al showed that quantitation of the therapeutic anti-TNF-α antibody, adalimumab, can be used to determine dosing intervals and to individualize disease control in patients with rheumatoid arthritis [20]. This approach requires reliable drug quantitation, even in the presence of nADA.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the recent paper of l‘Ami et al titled ‘Successful reduction of overexposure in patients with rheumatoid arthritis with high serum adalimumab concentrations: an open-label, non-inferiority, randomised clinical trial’ with interest 1. The topic of dose tapering is an important one and we welcome all research efforts in this field, especially controlled trials.…”
mentioning
confidence: 99%